EP-82 The First International Delphi Consensus Statement on Laparoscopic Gastrointestinal Surgery. (9th August 2022) - Omar, Islam; Madhok, Brijesh; Amr, Bassem; Pouwels, Sjaak; Graham, Yitka; Mahawar, Kamal
Abstract: Introduction: Laparoscopic surgery is now firmly established in the field of gastrointestinal (GI) surgery and has replaced open surgery in many areas. The purpose of this exercise was to prepare a consensus statement highlighting the important principles of laparoscopic GI surgery. Methods: A committee of 38 experts in laparoscopic GI surgery proposed and voted on 149 statements in two rounds following a modified Delphi protocol. Results: A consensus was achieved on 133 statements after two rounds. There was 100% consensus on informing the team of unusual complex operations, asking for a second opinion when needed and following the ergonomics principles. Additionally, 94.7% advised to have multiple options for abdominal entry, 100% agreed on tailoring the first port site to the patient, and 84.2% advised to use Veress needles with caution. Moreover, 97.4% consensus was reached on keeping the intra-abdominal pressure at the minimum required, and 92.1% agreed that a pressure of 12 mm Hg is adequate for most intra-abdominal surgery. There was a complete (100%) consensus on using cartridges of appropriate height, checking the doughnuts after using circular staplers, adding any foreign body inserted into the abdomen to the operating count, ensuring the integrity of instruments on removal from the abdomen, and avoiding handing over an operation in the middle. There was a 100% consensus on focusing on precision, not the speed, and learning to use the non-dominant hand effectively. Conclusion: A 38 experts achieved a consensus on 133 statements. Increased awareness of these should enhance the safety of patients undergoing laparoscopic surgery.